Pemanfaatan Aplikasi WPS dalam Meningkatkan Minat Belajar Siswa pada Materi Dongeng Bermuatan Bahasa Inggris di Era New Normal - Suhariyanti Suhariyanti; Sabrina Aulia Rahmah; Sarah Nasution (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
This study aimed to increase students’ interest in learning in English-filled fairy tale material using the WPS application. The research method used was the research and development method from Borg and Gall. The population in the study amounted to 72 students of grade 2 SD Amalyatul Huda. The samples specified in this study were 32 students and 2 teachers. Data analysis techniques were obtained from a team of material experts, design experts, Indonesian language teachers, and grade 2 students of SD Amalyatul Huda. The product produced from this research was in the form of a learning module. The results showed 1) validation from material experts including the feasibility of the content on average obtained 89.85% with good criteria, the average presentation feasibility was obtained 90.3% with very good criteria, and the assessment of linguistic aspects achieved on average 89.42 % with good criteria. (2) Validation of design experts with an average of 84.58% with good criteria. (3) the teacher's response got an average of 85.83% with good criteria. (4) student responses through individual trials obtained an average of 75% with sufficient criteria. (5) small group trials reached an average of 83.56% with good criteria. (6) limited test reaches an average of 94.92% with very good criteria. This proves that learning English-filled fairy tales using the WPS application has increased.